(Article Review): Crohn's Disease: Review about Crohn's Disease and Its Relation with Immunity - Al-Mayali , Zahraa Kareem; Ali, Rusul Arif Abd; Al-Kraity, Wijdan Rajh Hamza (Medical Science Journal for Advance Research, 2025)
Crohn's disease is a form of inflammatory intestinal illness can effect in in all region of the gastrointestinal tract. Also consider autoimmune disease. It has a complex genetic and environmental basis, but its precise cause is still idiopathic (unknown). The disease appears to originate by an unsuitable intestine's immune system for medications, toxins, infections, or intestinal bacteria in a genetically susceptible host. Crohn's illness is a complex disease with no notable cause. It is think to be produced from an aggregation of genetic, immune, and microbial environmental factors. Crohn's disease is distinguished by the presence of of mucosal ulceration and inflammation that can occur anywhere on the gastrointestinal tract, while most effect usually in the distal small intestine. Characterized by discontinuously transmural inflammation related to whole thickness of the intestine wall and an inflammatory response related with granulomas and lymphoid aggregative, that can generate many disorder like fistulas, abscesses and fibrotic strictures. Can be diagnosed by many methods like Laboratory examination , Histopathological examination Endoscopic examination and X-ray. Until this moment, the treatment of CD are yet under experience also can usage medication such as corticosteroids, immunosuppressants, anti-inflammatory drugs, and biological medicines to monitoring and decrease the symptoms. Concolusion: Crohn's illness is a chronic inflammatory sickness of the gut, considered an autoimmune disorder, which means the immune system erroneously attacks healthful tissue in human body. The cause of Crohn’s disease is due to a chronic inflammatory response that specifically impacts T lymphocytes, such as CD4 T lymphocytes. Activation of lymphocytes is the primary function of T cells; for Crohn Disease patients, T lymphocytes mainly produce IL-12, IFN-alpha, TNF-gamma, IL-1, IFN-gamma, and IL-2.